A palavra e o ato: memórias teatrais em Goiânia - DALLAGO, Saulo Germano Sales (2007)
The project A Palavra e o Ato: Memórias Teatrais em Goiânia ( The Word and the Act: Theatral Memories in Goiânia) is the result of a bibliographical research, directed by professor Márcio Pizarro Noronha, building a theoretical body for the analysis of verbal interviews collected from the artists and collaborators of the group Teatro Exercício from Goiânia and mainly from its major member, Hugo Zorzetti, director and dramatic writer of the trupe. The theories raised along their work go throughout the studies of memory, narrative and Art-History relations, on one side, and the studies of the non-verbal communication, performance of the social actor and the narrative as performance, on the other side, taking for scenary the constant relationship between the artist and the city, searching for the influences between them both and the expression of the environment through art. The theoretical quarrel happens, at a first moment, aside the empirical results. At a second moment the narrative of the memories of the interviewed individuals takes place while they tell the trajectory of the group since it was born, in the decade of the 70 s, during the fullness of Brazilian Military Dictatorship, going through the experience of the inclusion of the main artists of the company in a public cultural agency, finally reaching the attempt of the opening by the company of the Teatro da Liberdade ( Liberty Theater ), already in the end of the decade of the 80 s. The analysis of the interviews intends to search for the confrontation of these artists with the city of Goiânia, place of artistic accomplishments of the group, beginning with the analysis of their memories focused on the bias of the narrative, including all subjects and also to the bias of performance, in the case of previously cited Hugo Zorzetti, by the interlacement of historic, artistic, literary and sociological theories